GAMBARAN MENGENAI PERILAKU SEKS PRANIKAH PADA REMAJA DI SMA NEGERI 2 BANGKINANG - Guslian Rukmana; Yenny Safitri; Wanda Lasepa (Jurnal Spektrum Kesehatan Indonesia, 2026)
Premarital sexual behavior is behavior based on sexual urges or desires and seeking sexual pleasure through various behaviors, including intimate relationships. The purpose of this study was to analyze the overview of premarital sexual behavior among adolescents at SMA Negeri 2 Bangkinang City in 2024. This study used a quantitative design with a descriptive research design. The population was 256 eleventh-grade adolescents at SMA Negeri 2 Bangkinang City. The sample size was 156 individuals. Data analysis used univariate and bivariate analyses. The univariate analysis revealed that adolescents' reproductive health knowledge was in the poor category for 86 respondents (53.8%), and unhealthy sexual behavior for 82 respondents (52.6%). It is hoped that adolescents at SMA Negeri 2 Bangkinang Kota will maintain and improve their knowledge of reproductive health